From Midrash to Dialogue: Teaching Judaism in Interreligious Spaces. - Kamine, Benjamin (Ecumenical Review, 2022)
This article argues for the utility of teaching midrash when introducing Judaism in interreligious education programmes, based on the author's experiences with the interreligious course at the Ecumenical Institute at Bossey. Midrash illuminates many aspects of Jewish meaning‐making and provides students with multiple entry points based on their learning styles. It has also long played an important role in Jewish encounters with other religious communities. And it continues to frame how contemporary Jewish thinkers connect classical Jewish sources to modern challenges. The dialogical nature of midrash creates opportunities for the students and the instructor to seek mutual understanding, generating the potential for successful dialogue encounters outside the classroom. After reflecting on how the return to in‐person learning has expanded these possibilities, the author poses several questions for further inquiry.